Bone Marrow Microenvironment-On-Chip for Culture of Functional Hematopoietic Stem Cells - Sharipol, Azmeer; Lesch, Maggie L.; Soto, Celia A.; Frisch, Benjamin J. (Frontiers in Bioengineering and Biotechnology, 2022)
Hematopoiesis takes place in the bone marrow and is supported by a complex cellular and molecular network in the bone marrow microenvironment. Commonly used models of the human bone marrow microenvironment include murine models and two-dimensional and three-dimensional tissue cultures. While these model systems have led to critical advances in the field, they fail to recapitulate many aspects of the human bone marrow. This has limited our understanding of human bone marrow pathophysiology and has led to deficiencies in therapy for many bone marrow pathologies such as bone marrow failure syndromes and leukemias. Therefore, we have developed a modular murine bone marrow microenvironment-on-chip using a commercially available microfluidic platform. This model includes a vascular channel separated from the bone marrow channel by a semi-porous membrane and incorporates critical components of the bone marrow microenvironment, including osteoblasts, endothelial cells, mesenchymal stem cells, and hematopoietic stem and progenitor cells. This system is capable of maintaining functional hematopoietic stem cells in vitro for at least 14 days at frequencies similar to what is found in the primary bone marrow. The modular nature of this system and its accessibility will allow for acceleration of our understanding of the bone marrow.